Results from the UK Children's Cancer and Leukaemia Group study of extracranial germ cell tumours in children and adolescents (GCIII). (September 2019) - Depani, Sarita; Stoneham, Sara; Krailo, Mark; Xia, Caihong; Nicholson, James
Abstract: Background: For extracranial malignant germ cell tumours (MGCTs) in the UK, the GCII study used carboplatin-based chemotherapy (JEb) and demonstrated equivalent survival to cisplatin-containing protocols. GCIII, a single-arm observational study, used new risk stratification, replaced consolidation chemotherapy with a standard number of cycles and introduced surveillance for all stage I MGCTs. Pure teratomas were registered to understand their natural history. Methods: Patients with MGCTs were stratified to three risk groups – low risk (LR), intermediate risk (IR) and high risk (HR), using stage and prognostic factors. Patients with alpha fetoprotein (AFP) >10, 000 kU/L, stage IV disease (except testis <5 years and all germinomas) or stage II-IV mediastinal tumour were classified HR. Stage I tumours (LR) received chemotherapy only if disease progressed. IR and HR patients received 4 and 6 JEB cycles, respectively. Carboplatin dose was calculated using glomerular filtration rate to give an area under the curve of 7.9 ml/m 2 .min. Results: Eighty-six patients with MGCTs were enrolled from 2005 to 2009: 59% female, median age, 5.7 years. Twenty-five patients were LR, 21 IR and 38 HR. Seven LR patients had disease progression; all were successfully treated with chemotherapy. Overall survival (OS) for the whole group was 97%; 5-year event-free survival for JEb-treated patients was 92%, and OS, 95%. JEb was well tolerated with no observed significant hearing or renal side-effects. There was no discernible difference in carboplatin dose whether calculated by body surface area or creatinine clearance. Forty-seven patients with teratoma were managed with surgery and one had malignant transformation. Conclusion: Carboplatin-based chemotherapy as part of a risk-stratified approach leads to excellent survival in paediatric MGCTs, minimising potential burden of long-term effects. Highlights: Carboplatin is an effective treatment for paediatric extracranial germ cell tumours. An n+2 strategy of consolidation chemotherapy is unnecessary. Treatment can probably be safely de-escalated in germinomas. Carboplatin dosing of 600 mg/m 2 /cycle is reasonable for most patients.